Evaluation of the Pancasila Student Profile Strengthening Project Using the Discrepancy Evaluation Model - Khudin, Ilham Soleh; Sumedi, Sumedi; Muharramah, Nauriatul; Siregar, Ahmad Mukhlis (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to evaluate the activities of the Pancasila student profile strengthening project (P5) at SMP Muhammadiyah 2 Kalasan on the theme of local wisdom with the title of traditional games by using discrepancy evaluation model. This study used a descriptive qualitative approach with the data analysis techniques that included data summary, data presentation, conclusion drawing, and verification. The results of this study concluded that the design component focuses on the availability of documents, the implementers, and the input from students which later are compared with real implementation. Local wisdom was used for the P5 program theme with the aim to introduce the history of traditional games in Indonesia, foster the spirit of togetherness, promote traditional game culture, and increase students’ teamwork. In the installation component, it was concluded that the requirements and completeness of the project implementation were done by the P5 team with input from all 7th grade students. In the process component, it was concluded that the entire activities ran smoothly, but there was a gap as the post-test was not implemented. In the result component, it was concluded that the implementation of the P5 program on the theme of local wisdom focused on traditional games run as planned. The program is categorized as good and can be re-implemented, while still considering the evaluation of the program output.